Inoculum of indigenous microalgae/activated sludge for optimal treatment of municipal wastewaters and biochemical composition of residual biomass for potential applications. (October 2022) - Lima, Serena; Brucato, Alberto; Caputo, Giuseppe; Grisafi, Franco; Scargiali, Francesca
Abstract: In this work, municipal wastewater was treated with microalgal/activated sludge consortia. We aimed at obtaining a positive interaction between the microalgae and the heterotrophic bacteria and identifying the best combination for bioremediation purposes. A strain of Chlorella sp CW2 employed in this work was isolated from AS and molecularly characterised in this work for the first time. This strain and another previously isolated strain ( Chlorella sp Pozzillo) were inoculated alone and in combination with AS in different ratios in wastewaters. Microalgae/activated sludge growth curves were obtained by using a UV–vis spectrophotometer and a fluorimeter to distinguish the contribution of the photosynthetic microorganisms to the total growth. The effectiveness for the bioremediation of municipal wastewaters was evaluated by measuring the COD, the total nitrogen and total phosphorous content at the end of batch cultivations. Overall, the best abatement was achieved by the microalga Chlorella sp CW2 inoculated with activated sludge in the ratios 1:2 and 2:1, with a decrease of 81.39 % ± 0.56, 86.12 % ± 0.43, 82.89 % ± 2.66 and 82.5 % ± 0.83, 72.66 % ± 0, 46, 97.15 % ± 0.44 of COD, total nitrogen and total phosphorous, respectively. Finally, the residual biomass, constituted by a sludge enriched in microalgae, was analysed for its content in carbohydrates, lipids and fatty acid in order to suggest the best application for its valorisation. Considering the final composition of the obtained biomass and its remediation potential, the most promising sample may be the microalga Chlorella sp CW2 inoculated with activated sludge in the ratio 1:5. Graphical abstract: Unlabelled Image Highlights: Chlorella sp CW2 (CS) was isolated from activated sludge (AS). The remediation potentiality of AS with two Chlorella strains was assessed. The biochemical composition of the obtained biomass was determined. CS 1:5 is the most promising sample considering remediation and composition.